Implementação do Programa Fica Vivo!I : instituições, atores de contextos - Shirley Alexandra Ferreira (2012)
This dissertation aims to compare the implementation process of the Fica Vivo! Program in three different locations: Morro das Pedras, Cabana de Pai Tomás and Barreiro. For this purpose we sought to delineate explanatory factors that influenced the products obtained in the implementation process of Fica Vivo! Program both at central level and in the territories. Thus, the hypothesis that guided the study considered that the local implementation process of Fica Vivo! Program can be explained by contextual factors, institutional factors and by the actions of the implementers. That is, it was recognized that there are internal and external factors to public policy that hinder or facilitate its implementation and contribute to explain the reasons why they reached certain results rather than other possibles. For the work development is prized for conducting qualitative research from the semistructured interviews and document analysis. The results showed that there are many similarities and complementarities between of the implementation products analyzed locally.